Clinical features, hospitalisation and deaths associated with monkeypox: a systematic review and meta-analysis - Benites-Zapata, Vicente A. (2022)
Introduction: A multicountry monkeypox disease (MPX) outbreak began in May 2022 in Europe, leading to the assessment as a potential Public Health Emergency of International Concern (PHEIC) on June 23, 2022. Some observational studies have partially characterised clinical features, hospitalisations, and deaths. However, no systematic reviews of this MPX outbreak have been published. Methods: We performed a systematic review with meta-analysis, using five databases to assess clinical features, hospitalisations, complications and deaths of MPX confirmed or probable cases. Observational studies, case reports and case series, were included. We performed a random-effects model meta-analysis to calculate the pooled prevalence and 95% confidence interval (95% CI). In addition, we carried out a subgroup analysis according to the continents and a sensitivity analysis excluding studies classified as having a high risk of bias. Results: A total of 19 articles were included, using only 12 articles in the quantitative synthesis (meta-analysis). For 1958 patients, rash (93%, 95% CI 80–100%), fever (72%, 95% CI 30–99%), pruritus (65%, 95% CI 47–81%), and lymphadenopathy (62%, 47–76%), were the most prevalent manifestations. Among the patients, 35% (95% CI 14–59%) were hospitalised. Some 4% (95% CI 1–9%) of hospitalised patients had fatal outcomes (case fatality rate, CFR). Conclusion: MPX is spreading rapidly, with a third of hospitalised patients, but less than 5% with fatal outcomes. As this zoonotic virus spreads globally, countries must urgently prepare human resources, infrastructure and facilities to treat patients according to the emerging guidelines and the most reliable clinical information.